Resultant Effect of Crisis-Driven HR Strategies Applied During Current Economic Crisis in Oman – An HR Manager’s Perspective - Thumiki, Venkat Ram Raj; Jovancai Stakić, Ana; Al Barwani, Rayaan Said Sulaiman (The European Journal of Applied Economics, 2019)
During an economic crisis, companies redesign their functional strategies for survival and growth. This paper aims at identifying HR practices adopted during the current economic crisis in Oman, and explains the resultant effect of crisis-driven HR strategies from an HR managers’ perspective. Primary data was collected online from 112 HR manag-ers representing various manufacturing and service organizations in Muscat, Oman. It was found that HR managers perceive a greater im-pact of economic crisis on their businesses rather than other types of crises such as natural and technology crises. They think that managing employees during an economic crisis is relatively easier than managing other resources and other stakeholders. Changing HR practices during economic crises include, abeyance of employee benefits and cutting costs on employee recreation. Knowledge management activities have been increased and non-monetary motivation techniques are being adopted as a part of crisis-driven HR management. Increased employee engage-ment and enhanced corporate image among employees were identified as the resultant effect. Testing the hypothesis revealed that cost cutting on employee recreation is significantly higher in large organizations, job redesign activity is significantly higher in small organizations, while large organizations find it difficult to deal with employees during pe-riods of crisis more so than small and medium sized organizations do.